2005
DOI: 10.1016/s1808-8694(15)31336-7
|View full text |Cite
|
Sign up to set email alerts
|

Nasal endoscopy associated with paranasal sinus computerized tomography scan in the diagnosis of chronic nasal obstruction

Abstract: Thus, the presented study and the results of nasal fossa findings obtained by nasal endoscopy were more conclusive in the elucidation of diagnosis than those obtained by computer tomography of the paranasal sinus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 3 publications
1
8
0
4
Order By: Relevance
“…Most patients show turbinate hypertrophy by endoscopy compared to the same affection at CT scan [13]. In the current study, the finding of hypertrophic concha was more evidenced in CT scan compared to sinus endoscopy (43.75 vs. 40 %).…”
Section: Discussionsupporting
confidence: 39%
“…Most patients show turbinate hypertrophy by endoscopy compared to the same affection at CT scan [13]. In the current study, the finding of hypertrophic concha was more evidenced in CT scan compared to sinus endoscopy (43.75 vs. 40 %).…”
Section: Discussionsupporting
confidence: 39%
“…Geminiani, et al [17] Jiannetto and Pratt, [18] Duarte, [19] reported that patients who had negative CT scans, showed endoscopic exams with nasal polyposis and septum deviation. Duarte, [19] in which 16 (80%) out of 20 patients showed turbinate hypertrophy evidenced by nasofibroscopy and only nine (45%) of 20 patients showed the same affection at CT scan.…”
Section: Present and Past Historymentioning
confidence: 99%
“…Computed tomography (CT) is one of the most important diagnostic tools in medicine, with a wide scope for clinical use [4, 5]. In 2009, Brazil had 15.6 CT scanners (CTs) per million people, a density comparable to Canada (14.2) and New Zealand (15.8).…”
Section: Introductionmentioning
confidence: 99%